477 Evaluating the therapeutic efficacy of combination IL-12 and trabectedin for the treatment of triple negative breast cancer - Emily Schwarz; Himanshu Savardekar; Sara Zelinskas; Abigail Mouse; Lianbo Yu; Gregory Behbehani; Timothy Cripe (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: IL-12 has potent immune effects but the presence of myeloid-derived suppressor cells (MDSC) can inhibit IL-12-induced NK cell cytotoxicity. Thus, we hypothesized that combining IL-12 with trabectedin, an immunosuppressive myeloid cell depleting agent, would improve its therapeutic efficacy in triple negative breast cancer (TNBC). METHODS/STUDY POPULATION: Combination IL-12 and trabectedin was tested in the 4T1 mouse model of TNBC. 4T1 cells were injected into the mammary fat pad of female BALB/cj mice. When tumors reached 50 mm3, mice were randomly divided into 4 groups and treated with PBS, IL-12 (0.5 μg/mouse 3x/wk), 0.15 mg/kg trabectedin weekly or the combination. Tumor volumes were measured by calipers. Mass cytometry was performed on spleens and tumors using a 35-antibody panel. Plasma IFN-γ levels were measured by ELISA. The role of NK cells was evaluated via depletion with anti-asialo-GM1. The Luminex Discovery Assay was used to measure plasma cytokines and immunohistochemistry was performed for CD4 and CD8a. Linear/nonlinear mixed effects modeling was used for in vivo data analysis and applicable t- or ANOVA tests were used for in vitrodata analysis. RESULTS/ANTICIPATED RESULTS: Combination IL-12 and trabectedin led to a significant reduction in tumor burden compared to single-agent IL-12, trabectedin and control treatments (all p<0.001), as well as higher levels of IFN-γ (all p<0.04). One combination treated mouse had complete tumor regression. Splenic MDSC were significantly decreased in combination treated mice. NK depletion abrogated the effects of combination therapy. Compared to mice receiving a control antibody, NK depletion of combination treated mice led to lower levels of CCL5 (p<0.01) and CXCL10 (p<0.001) and significantly higher tumor burden (p=0.001). CD8+T cell levels were significantly higher in combination treated mice compared to those receiving IL-12 (p<0.01), and these levels were decreased when mice were depleted of NK cells (p=0.01). DISCUSSION/SIGNIFICANCE: TNBC represents 15% of all breast cancer diagnoses and is associated with a worse prognosis compared to other subtypes. Black women are twice as likely to be diagnosed with TNBC and more likely to die from disease than White women. Thus, there is an increasing need to develop additional therapeutic options for this disease.